A Pronator Teres–sparing Volar Approach for Osteosynthesis of Midshaft Diaphyseal Radius Fractures. Issue 4 (December 2015) - McLean, James M.; Stevenson, Aaron W.; Samson, Anthony; Watts, Adam C.; Daneshvar, Parham; Constant, Christopher R.
Abstract : Henry's approach is widely considered the "workhorse" for exposing the volar radius and has not really changed since his original description in 1945. We describe a pronator teres–sparing volar approach to the forearm, for osteosynthesis of midshaft diaphyseal radius fractures. We believe this approach is safe, simple, and reproducible, and has several practical and theoretical advantages over Henry's original description. Abstract : Supplemental Digital Content is available in the text.